Caracterização química de resíduos do cultivo de abacaxi e de sementes de guaraná: contribuição para maximizar o aproveitamento de biomassas na agroindústria brasileira - Gondim, Tamyris de Aquino (2024)
The need for agribusiness to meet the growing demand for food results in pressure to increase and maximize its productivity alongside the development of new products. In these aspects, factors such as sustainability and the selection of the best clones with different specific purposes are of great relevance. Sustainability is an extremely important issue, mainly aimed at reusing the millions of tons of agro-industrial waste generated continuously during agricultural production. However, for waste to be reused efficiently, it is essential that the chemical and biological characteristics of the waste are determined. In this context, this work aims to establish the metabolic and mineral profiles of pineapple leaves (Ananas comosus) of seven commercial pineapple varieties and an assessment of cytotoxicity. The metabolic profiles of pineapple leaves were established using UPLC-QTOF-MSE, where twenty-eight metabolites were noted. On the other hand, the minerals were evaluated using ICP-OES, where it was possible to determine and quantify Zn, Cr, Cd, Mn, P and Fe. In the chemometric analysis designed using PCA and HCA, it was possible to verify that Pineapple leaves have similarities and differences in relation to their chemical composition. The hydroethanolic extracts of pineapple leaves evaluated showed low levels of cytotoxicity. This fact combined with the chemical composition that was determined can support the prospect of new uses and applications of this co-product in different types of industries, such as pharmacology, cosmetics and food. In addition, seeds of different clones of guaraná (Paullinia cupana) were studied, attributed to high levels of caffeine in their composition. Therefore, the seeds of fifty-six different guarana clones were evaluated. With this, the metabolomic profile of guaraná seeds was traced through UPLC-QTOF-MSE, which led to the annotation of nineteen specialized metabolites. Furthermore, targeted metabolomics was also used, leading to the identification and quantification of metabolites by NMR. A multivariate analysis was also designed, elucidating the similarities and differences between the guaraná seeds evaluated, mainly with regard to the concentration levels of the metabolites. Thus, it is concluded that evaluating and determining the metabolic specificities of different guaraná clones allows their application in the development of products with different levels of specific metabolites, such as caffeine. This can serve different purposes in the food industry, such as the development of products with low or high caffeine content. In general, we can verify that pineapple leaves and guaraná seeds can be established, respectively, as a co-product and a product of agro-industrial interest, either as a source of bioactive compounds or in the development of new food products.